Las estrofas 4-6 de las Coplas de Manrique a la luz de una lectio de la Glosa famosíssima de Alonso de Cervantes - González, Javier Roberto (2020)
Fil: González, Javier Roberto. Pontificia Universidad Católica Argentina; Argentina